З історії вивчення та вшанування Т. Г. Шевченка на Буковинській Гуцульщині - Меленчук, О.В. (Слово і Час, 2019)
У статті розглядається внесок випускників Чернівецького університету, колишніх учнів С. Смаль-Стоцького, а саме Д. Лукіяновича, І. Дощівника, С. Лакусти, М. Павлусевича, які своєю творчою й педагогічною діяльністю залишили помітний слід у справі популяризування та вивчення творчості Т. Шевченка на теренах Буковини. Виокремлено вижницький осередок, де розгорталася педагогічна і творча діяльність згаданих осіб. З’ясовано їхні погляди, оцінки творів поета, основні ідеї та цінність літературно-критичних матеріалів, художніх творів у розвиткові наукової та популяризаторської шевченкіани. The paper informs about the cultural contribution of Chernivtsi University graduates, former S. Smal-Stotskyі’s students D. Lukiianovych, I. Doshchivnyk, S. Lakusta, and M. Pavlusevych, whose creative work and pedagogical activity played an important role in promoting and exploring the works by T. Shevchenko in the territories of Bukovyna. Focusing on Vyzhnytsia center, the paper clarifies fundamental views of the mentioned persons, their assessments of the poet’s works and main relevant ideas. The author evaluates critical writings and literary works of the Bukovynians in relation to the development of Shevchenko studies and promotion of his legacy.At the late 19th and early 20th century none of the Ukrainian universities focused on Shevchenko’s works more than Chernivtsi University. Hnat Onyshkevych initiated a series of lectures on the study of T. Shevchenko’s poetic works. His project was continued by professor S. Smal-Stotskyi, who offered the course “Taras Shevchenko. Life and Works” and held a series of seminars on the theme “Shevchenko’s Poetry” at the beginning of the 20th century. Those who studied at the Philosophical Faculty of Chernivtsi University picked up the teachings of Professor S. Smal-Stotskyі and showed unceasing interest in the works by T. Shevchenko. In the conditions of the national cultural revival, Shevchenko’s poems were especially significant; the poet’s crystallized ideas passed from teacher to student and played an important role in forming a new generation of conscious Ukrainians who were concerned about the future of their country. There were two circles (Kitsman-Kolomyia and Vyzhnytsia) in Bukovyna where researchers and promoters of T. Shevchenko’s works made the poet’s legacy actual and contributed to Shevchenko studies. The paper summarizes the achievements of the Vyzhnytsia center representatives.